KOMUNIKASI INTERPERSONAL PELAYAN DENGAN PELANGGAN DALAM MEMPERTAHANKAN BRAND TRUST DI RESTO SALIRA - Elyasaf Bintang Wibowo; Andri Astuti Itasari (Solidaritas, 2025)
Brand trust is one of the crucial factors for sustaining business in the culinary sector. Thisstudy aims to analyze the role of interpersonal communication between waiters and customers atResto Salira in maintaining brand trust. The research applied a descriptive qualitative method witha case study design. Data were collected through in-depth interviews with the supervisor, waiters,and customers, as well as observations and documentation of Google Reviews. Data validity wastested using source triangulation. The findings reveal that waiters at Resto Salira demonstrateinterpersonal communication through friendliness, quick responses, polite verbal interaction, andsupportive nonverbal cues. Analysis using Devito’s interpersonal communication theory indicatesthat four indicators (openness, supportiveness, positiveness, and equality) are applied, whileempathy is not fully optimized. In conclusion, interpersonal communication significantlycontributes to building customer brand trust, although further improvement in empathy is neededto strengthen overall trust.Keywords: Brand Trust, Interpersonal Communication, service, Resto Salira.